Development of a method based on high‐performance liquid chromatography coupled with diode array, fluorescence, and mass spectrometric detectors for the analysis of eosin at trace levels. Issue 6 (2nd April 2020) - Sabatini, Francesca; Degano, Ilaria; Colombini, Maria Perla
Abstract: Eosin (Acid Red 87, C.I. 45380) is one of the most brilliant and challenging early synthetic dyes. In this study, an analytical approach based on high‐performance liquid chromatography coupled with diode array and fluorescence detector and high resolution mass spectrometry was developed for testing different analytical columns and acids in the mobile phase. The ultra‐sensitive approach, based on a chromatographic separation on a solid core and a porous shell Poroshell 120 EC‐C18, allowed us to detect and characterize eosin and its synthesis by‐products, such as the debrominated and methyl ester forms of eosin, in trace levels (the limit of detection for eosin is 0.13 ppb). The resulting miscellaneous composition of the eosin standard highlights the importance to determine the exact composition of the starting material to deal with, in order to avoid misinterpretations in aged or degraded samples. Finally, the successful identification of eosin in few grains (approximatively 20 × 40 μm wide) of a faded Van Gogh's painting proved the strengths of our approach.